Megachiropteran diversity patterns and processes in oil palm production landscape - Che Shaffine, Muhamad Syafiq (2017)
Oil palm industry is one of the main economic drivers in Southeast Asia. It has caused tropical deforestation on a massive scale in producing countries. Forest conversion to commercial oil palm agriculture has decimated habitats of countless native flora and fauna species. Large-scale plantations and smallholdings are two distinctive oil palm production systems. Smallholdings would host a greater biodiversity than large-scale plantations. Habitat complexity in smallholdings is influenced by multiple farming practices (i.e. polyculture and monoculture). However, little is known on the effects of such farming practices in oil palm smallholdings on mammal biodiversity, particularly megachiropteran bats. This study aimed to find the best farming practice to reconcile oil palm production and biodiversity conservation. Mist-nets were used to trap frugivorous bats at 120 smallholdings in Peninsular Malaysia. The species richness and abundance of frugivorous bats between monoculture and polyculture smallholdings were compared and their relationships with vegetation structure characteristics were investigated. The results revealed that species richness (total megachiropteran bat species) and abundance (total individual from each species of megachiropteran bat) were significantly greater in polyculture smallholdings than monoculture smallholdings. The result also found that 28.21% of the model variations in species richness were explained by the habitat characteristics measured including the number of dead standing oil palms and immature oil palms, non-grass cover, height of non-grass cover, and farming practice. This shows greater habitat complexity is required for the maintenance of frugivorous bats. Therefore, in order to conserve farmland biodiversity in oil palm production landscapes, either smallholding or plantation, commercial growers should implement polyculture rather than monoculture farming.